Redefining outcomes of ventricular arrhythmia for SGLT2 inhibitor medication in heart failure patients: a meta-analysis of randomized controlled trials - Miao Lin; Shiyu Zhang; Lu Zhang; Chengying Yang; Yang Luo; Yajin Peng; Xiaoqiu Tan; Qiang Wen; Xinrong Fan; Xianhong Ou (Systematic Reviews)
Abstract Background Sodium-glucose co-transporter 2 (SGLT2) inhibitors have been shown to lower the risk of re-hospitalization and cardiovascular mortality among heart failure (HF) patients. Nevertheless, the impact of these agents on ventricular arrhythmias (VAs) has not been thoroughly investigated. To assess the beneficial impact of SGLT2 inhibitors on VAs in patients at various stages of HF, a systematic review and meta-analysis of randomized controlled trials involving SGLT2 inhibitors in this patient population was performed. Methods A comprehensive search of the PubMed, Embase, Ovid, ProQuest, Scopus, and Cochrane databases was performed for clinical trials published up to November 21, 2024. The primary outcomes of interest were incidences of VAs and sudden cardiac death (SCD) between the groups receiving SGLT2 inhibitors and the control drugs. For the outcomes observed in the populations of the included trials and in specific subgroups, hazard ratios (HRs) and 95% confidence intervals (CIs) were pooled and meta-analysed across the analyses. Results A total of 23 randomized trials (22 placebo-controlled trials and 1 active-controlled trial) involving 74,380 patients (37,372 receiving SGLT2 inhibitors and 37,008 in the control group) were included. The analysed SGLT2 inhibitors included canagliflozin, dapagliflozin, empagliflozin, bexagliflozin, sotagliflozin, and ertugliflozin. The participants were non-advanced HF patients, including at-risk for HF, pre-HF, and symptomatic HF, with follow-up duration ranging from 12 to 296 weeks. Compared with the control, treatment with SGLT2 inhibitors was associated with significantly reduced risk of VAs (risk ratio (RR) 0.85, 95% confidence interval (CI) 0.74–0.98; P = 0.02) and SCD (RR 0.79, 95% CI 0.64–0.98; P = 0.03). Subgroup analyses indicated that longer follow-up (≥ 1 year) taking SGLT2 inhibitors can still reduce the risk of VAs (RR 0.79, 95% CI 0.65–0.96; P = 0.02) and SCD (RR 0.80, 95% CI 0.65–0.99; P = 0.04). Conclusion SGLT2 inhibitors have beneficial effects on lowering risks of VAs and SCD in patients with type 2 diabetes, cardiovascular diseases, heart failure with reduced ejection fraction (HFrEF), heart failure with preserved ejection fraction (HFpEF), and heart failure with mildly reduced ejection fraction (HFmrEF), with longer follow-up duration reinforcing these findings. However, future prospective trials are needed to verify the effects of SGLT2 inhibitors on VAs and SCD. Systematic review registration PROSPERO (CRD42024601914)